CONTRAST ENHANCED SPECTRAL MAMMOGRAPHY (CESM) (REVIEW) - N. I. Rozhkova; I. I. Burdina; S. B. Zapirova; M. L. Mazo; S. P. Prokopenko; O. E. Yakobs (Исследования и практика в медицине)
The problem of early diagnosis of a breast cancer is extremely actual. Growth of incidence at women from 19 to 39 years increased for 34% over the last 10 years. It defines need of acceleration of development and deployment of the latest technologies of identification of the earliest symptoms of diseases. The x-ray mammography is the conducting method among of all radiological methods of diagnostics. Nevertheless a number of restrictions of method reduces its efficiency. The technologies increasing informational content of x-ray mammography – the leading method of screening – due to use of artificial contrasting and advantages of digital technologies are constantly developed. In this review it is described works, in which the authors having clinical experience of application of CESM – contrastenhanced spectral mammography on representative group of women. Positive sides and restrictions of new technology in comparison with mammography, ultrasonography and MRT are shown in this article.